PERKEMBANGAN MUHAMMADIYAH DI DESA GANTIWARNO KECAMATAN PEKALONGAN KABUPATEN LAMPUNG TIMUR TAHUN 2000-2021 - Ardi Firanata; Kuswono Kuswono (Swarnadwipa, 2019)
The purpose of this research is to find out "Study of the History of MuhammadiyahDevelopment in the Village of Gantiwarno. This research uses descriptive qualitative research, with historical research methods through four stages of work, namely heuristics (collection of sources), The research provides information about the development of Muhammadiyah in the village ofgantiwarno. The background of the entry of Muhammadiyah in the village ofgantiwarno, sub-district of Pekalongan, is due to the condition of the religious life of the people who are still influenced by ancestral beliefs (animism and dynamism as well as the influence of Hindu-Buddhist teachings and the influence of Dutch government power. The development of Muhammadiyah ingantiwarno Village can be divided into two, namely the vertical development of Muhammadiyah development ingantiwarno Village. Pekalongan District, namely the establishment of the Muhammadiyah Branch ofgantiwarno, while horizontally the development of Muhammadiyah in the village ofgantiwarno can be seen from the business charity Muhammadiyah as in the field of education and religion (da'wah). The role of Muhammadiyah in the field of education and religion in the village ofgantiwarno, Pekalongan district, has made rapid progress. This can be seen from the establishment of Muhammadiyah schools in the village ofgantiwarno and the establishment of mosques and prayer rooms.